Exaggerated postural vasoconstrictor reflex in Raynaud's phenomenon. Issue 6581 (9th May 1987) - Olsen, N; Petring, O U; Rossing, N
Abstract : The central and local regulation of capillary blood flow in the finger was studied by the local xenon-133 washout technique in women with primary Raynaud's phenomenon, men with vibration induced white finger, and their respective sex matched controls. The vasoconstrictor response to venous stasis of 40 mm Hg elicited by local reflex was normal in both types of Raynaud's phenomenon. Change in posture from lying to sitting induced vasoconstriction in all groups, which was abolished by proximal nervous blockade. The vasoconstrictor response to sitting was augmented in both groups of subjects with Raynaud's phenomenon compared with their sex matched controls. These results show the existence of central and local postural vasoconstrictor reflexes in normal fingers. In both types of Raynaud's phenomenon there was hyperreactivity of the central sympathetic nervous system to orthostatic stress and normal function of digital arterioles and postganglionic sympathetic nerve fibres.